Sidelined Investors, Trading-Generated News, and Security Returns - Cao, H. Henry; Coval, Joshua D.; Hirshleifer, David (Review of Financial Studies, 2002)
This article studies information blockages and the asymmetric release of information in a security market with fixed setup costs of trading. In this setting, “sidelined” investors may delay trading until price movements validate their private signals. Trading thereby internally generates the arrival of further news to the market. This leads to (1) negative skewness following price run-ups and positive skewness following price rundowns (even though the model is ex ante symmetric), (2) a lack of correspondence between large price changes and the arrival of external information, and (3) increases in volatility following large price changes.